Surface characterization of human serum albumin and sodium perfluorooctanoate mixed solutions by pendant drop tensiometry and circular dichroism - Messina, Paula Verónica (2006)
The interfacial behavior of mixed human serum albumin (HSA)/sodium perfluorooctanoate (C8FONa) solutions is examined by using two experimental techniques, pendant drop tensiometry and circular dichroism spectroscopy. Through the analysis of the surface tension of the mixed solutions, surface competitive adsorption at the air-water interface between C8FONa and HSA is detected. The dynamic adsorption curves exhibit the distinct regimes in their time-dependent surface tension. The nature of these regimes is further analyzed in terms of the variation of the molecules surface areas. As a consequence, a compact and dense structure was formed where protein molecules were interconnected and overlapped. Thus, a reduction of the area occupied per molecule from 100 to 0.2 nm2 is interpreted as a gel-like structure at the surface. The presence of the surfactant seems to favor the formation of this interfacial structure. Finally, measurements of circular dichroism suggests a compaction of the protein due to the association with the surfactant given by an increase of α-helix structure in the complexes as compared to that of pure protein.